Digital interventions to promote psychological resilience: a systematic review and meta-analysis - Sarah K. Schäfer; Lisa von Boros; Lea M. Schaubruch; Angela M. Kunzler; Saskia Lindner; Friederike Koehler; Tabea Werner; Federico Zappalà; Isabella Helmreich; Michèle Wessa; Klaus Lieb; Oliver Tüscher (npj Digital Medicine, 2024)
Abstract Societies are exposed to major challenges at an increasing pace. This underscores the need for preventive measures such as resilience promotion that should be available in time and without access barriers. Our systematic review summarizes evidence on digital resilience interventions, which have the potential to meet these demands. We searched five databases for randomized-controlled trials in non-clinical adult populations. Primary outcomes were mental distress, positive mental health, and resilience factors. Multilevel meta-analyses were performed to compare intervention and control groups at post-intervention and follow-up assessments. We identified 101 studies comprising 20,010 participants. Meta-analyses showed small favorable effects on mental distress, SMD = –0.24, 95% CI [–0.31, –0.18], positive mental health, SMD = 0.27, 95% CI [0.13, 0.40], and resilience factors, SMD = 0.31, 95% CI [0.21, 0.41]. Among middle-aged samples, older age was associated with more beneficial effects at follow-up, and effects were smaller for active control groups. Effects were comparable to those of face-to-face interventions and underline the potential of digital resilience interventions to prepare for future challenges.